Two new species of the genus Mitjaevia Dworakowska from China (Hemiptera: Cicadellidae: Typhlocybinae) - Song, Yuehua; Li, Zizhong; Xiong, Kangning (Zootaxa, 2011)
Two new species from China are added to the genus Mitjaevia Dworakowska, 1970 (Hemiptera: Cicadellidae: Typhlocybinae), M. protuberanta sp. n. and M. wangwushana sp. n. A key to distinguish all species of the genus is provided.